2017
DOI: 10.1007/s10936-017-9554-3
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Ambiguity: Do Multiple Meanings Inhibit or Facilitate Word Recognition?

Abstract: It is not clear whether multiple unrelated meanings inhibit or facilitate word recognition. Some studies have found a disadvantage for words having multiple meanings with respect to unambiguous words in lexical decision tasks (LDT), whereas several others have shown a facilitation for such words. In the present study, we argue that these inconsistent findings may be due to the approach employed to select ambiguous words across studies. To address this issue, we conducted three LDT experiments in which we varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
8
12
0
2
Order By: Relevance
“…The picture is complicated, however, by inconsistent previous findings regarding the impact of number of senses. This variable is modulated by other factors such as task demands, relatedness of meanings, method for defining number of senses, and type of distractors; in some cases, words with more senses actually show an advantage (e.g., Azuma & Van Orden, 1997; Borowsky & Masson, 1996; Haro & Ferré, 2018; Piercey & Joordens, 2000; Rodd, Berriman, Landau, Lee, Ho, Gaskell & Davis, 2012; Rodd, Gaskell & Marslen-Wilson, 2002). Thus, it cannot be definitively concluded whether the larger number of senses for verbs in this study influenced the grammatical class effect.…”
Section: Discussionmentioning
confidence: 99%
“…The picture is complicated, however, by inconsistent previous findings regarding the impact of number of senses. This variable is modulated by other factors such as task demands, relatedness of meanings, method for defining number of senses, and type of distractors; in some cases, words with more senses actually show an advantage (e.g., Azuma & Van Orden, 1997; Borowsky & Masson, 1996; Haro & Ferré, 2018; Piercey & Joordens, 2000; Rodd, Berriman, Landau, Lee, Ho, Gaskell & Davis, 2012; Rodd, Gaskell & Marslen-Wilson, 2002). Thus, it cannot be definitively concluded whether the larger number of senses for verbs in this study influenced the grammatical class effect.…”
Section: Discussionmentioning
confidence: 99%
“…There still lacks a definite theoretical formulation which can be used to predict the interaction among the multiple meanings of L2 ambiguous words. In the field of word recognition, some studies have found differences between processing unambiguous words and ambiguous words (Klepousniotou and Baum, 2007;Klepousniotou et al, 2012;Haro and Ferré, 2018;Haro et al, 2019). For example, it takes less time to recognize ambiguous words than unambiguous words (Borowsky and Masson, 1996;Hino and Lupker, 1996;Haro and Ferré, 2018;Haro et al, 2019).…”
Section: The Current Studymentioning
confidence: 99%
“…In the field of word recognition, some studies have found differences between processing unambiguous words and ambiguous words (Klepousniotou and Baum, 2007;Klepousniotou et al, 2012;Haro and Ferré, 2018;Haro et al, 2019). For example, it takes less time to recognize ambiguous words than unambiguous words (Borowsky and Masson, 1996;Hino and Lupker, 1996;Haro and Ferré, 2018;Haro et al, 2019). Moreover, some studies further found homonym disadvantage and polysemy advantage compared to processing unambiguous words (Rodd et al, 2002;Beretta et al, 2005).…”
Section: The Current Studymentioning
confidence: 99%
“…Hence, despite having two different meanings linguistically, the word despecho can be said to have only the psychological meaning of the negative affective state. For further discussion of the pros and cons of the dictionary and subjective approaches, see Fraga, Padrón, Perea, and Comesaña (2017), Haro and Ferré (2018), and Haro et al (2017). 2.…”
Section: Limitations and Conclusionmentioning
confidence: 99%